The Nrf2-Antioxidant Response Element Signaling Pathway Controls Fibrosis and Autoimmunity in Scleroderma - Kavian, Niloufar; Mehlal, Souad; Jeljeli, Mohamed; Saidu, Nathaniel Edward Bennett; Nicco, Carole; Cerles, Olivier; Chouzenoux, Sandrine; Cauvet, Anne; Camus, Claire; Ait-Djoudi, Mehdi; Chéreau, Christiane; Kerdine-Römer, Saadia; et al. (Frontiers in Immunology, 2018)
Systemic sclerosis (SSc) is an auto-immune disease with fibrosis of the skin and internal organs and vascular alterations. Dysregulations in the oxidant/anti-oxidant balance are known to be a major factor in the pathogenesis of the disease. Indeed, Reactive oxygen species (ROS) trigger neo-epitopes leading to a breach of immune tolerance and autoimmune responses, activate fibroblasts to proliferate and to produce excess of type I collagen. ROS also alter endothelial cells leading to vascular dysfunction. Glutathione (GSH) is the most potent anti-oxidant system in eukaryotic cells. Numerous studies have reported a defect in GSH in SSc animal models and humans, but the origin of this defect remains unknown. The transcription factor Nrf2 is a key player in the anti-oxidant defense, as it can induce the transcription of anti-oxidant and cytoprotective genes through its interaction with the antioxidant-response elements. In this work we investigated whether Nrf2 could be implicated in the pathogenesis of SSc, and if this pathway could represent a new therapeutic target in this orphan disease with no curative medicine. Skin biopsies from 13 patients and 10 controls were harvested, and skin fibroblasts were extracted. Experimental SSc was induced both in BALB/c and in Nrf2-/- mice by daily intra-dermal injections of Hypochloric acid. In addition, diseased BALB/c mice were treated with an Nrf2 agonist, dimethyl-fumarate or placebo. A drop in Nrf2 and target genes mRNA levels was observed in skin fibroblasts of SSc patients compared to controls. Moreover, the Nrf2 pathway is also downregulated in skins and lungs of SSc mice. In addition, we observed that Nrf2-/--mice have a more severe form of SSc with increased fibrosis and inflammation compared to wild type SSc mice. Diseased mice treated with the Nrf2 agonist DMF exhibited reduced fibrosis and immune activation compared to untreated mice. The ex vivo treatment of skin fibroblasts from SSc mice with DMF restores GSH intra-cellular content, decreases ROS production and cell proliferation. These results suggest that the Nrf2 pathway is highly dysregulated in human and mice SSc with deleterious consequences on fibrosis and inflammation and that Nrf2 modulation represents a therapeutic target in SSc.